Beyond genetics: can micro and nanoplastics induce epigenetic and gene-expression modifications? - Poma, Anna M. G.; Morciano, Patrizia; Aloisi, Massimo (Frontiers in Epigenetics and Epigenomics, 2023)
Plastic pollution is becoming a worldwide crisis. It can be found in all environmental matrices, from the seas to the oceans, from dry land to the air we breathe. Because of the various types of plastic polymers and waste degradation methods, the types of plastic particles we are exposed to are quite diverse. Plants and animals are continuously exposed to them, and as the top of the food chain, humans are as well. There are numerous studies that confirm the toxicity of these contaminants, yet there is still a significant vacuum in their epigenetics effects and gene expression modifications. Here we collect studies published to date on the epigenetics effects and gene expression modulation induced by micro and nanoplastics. Although published data are still scarce, it is becoming evident that micro- and nanoplastics, whether acutely or chronically administered, do indeed cause such changes in various model organisms. A future challenge is represented by continuing and deepening these studies to better define the molecular mechanisms underlying the observed toxic effects and above all to translate these results to humans to understand their impact on health.